The XIX International Conference on Electrical Machines - ICEM 2010 2010
DOI: 10.1109/icelmach.2010.5608078
|View full text |Cite
|
Sign up to set email alerts
|

Brushless DC motor with a bonded permanent magnet and powder magnetic core

Abstract: Φ Abstract -Powder magnetic circuits find more and more application in modern electric machines. These magnetic circuits frequently comprise soft magnetic core and powder permanent magnets as a source of magnetic flux of excitation. It is connected with a lot of advantages of these kinds of materials. The main purpose of the work is to design a brushless DC motor with powder permanent magnet and powder soft magnetic core. It was assumed that the powder magnetic core will be prepared from iron powder bonded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Future work will regard the adoption of different binders for the realization of bonded magnets and different magnetization patterns [24], [40], as well as the possibility to realize machines with magnetic circuits constituted by soft magnetic composites [41]- [44].…”
Section: ) For What It Concerns the Efficiency Value As Alreadymentioning
confidence: 99%
“…Future work will regard the adoption of different binders for the realization of bonded magnets and different magnetization patterns [24], [40], as well as the possibility to realize machines with magnetic circuits constituted by soft magnetic composites [41]- [44].…”
Section: ) For What It Concerns the Efficiency Value As Alreadymentioning
confidence: 99%
“…The rotor is made of a permanent magnet material, Neodymium Ferric Boron (NdFeB) and the magnets are usually surface mounted [4]. Unlike conventional motors, BLDC motors require rotor position sensing, which is done using the Hall effect sensors mounted on the stator surface [5].…”
Section: A Operation Of Bldc Motormentioning
confidence: 99%
“…The variation of L ds and L qs with θ e can be neglected with the use of non-salient pole machines, where L ds =L qs =L s [8] or with the use of high coercive PM material [4], [5]. As a result, the electromagnetic torque equation for BLDC motor is given by (9).…”
Section: A Proposed Dtc Techniquementioning
confidence: 99%
“…OFT MAGNETIC COMPOSITE (SMC) CORES composed of magnetic particles coated by electrically insulating and non-magnetic material have advantages over traditional laminated steels used in electromagnetic machines such as motors and reactors [1], [2]: the former has lower eddy current losses and is adequate for forming 3D shapes [3]. It is experimentally shown that the macroscopic permeability and eddy current losses in SMC depend on the density, size and shape of the magnetic particles.…”
Section: Introductionmentioning
confidence: 99%